2021
DOI: 10.3390/ijms22116140
|View full text |Cite
|
Sign up to set email alerts
|

RbfA Is Involved in Two Important Stages of 30S Subunit Assembly: Formation of the Central Pseudoknot and Docking of Helix 44 to the Decoding Center

Abstract: Ribosome biogenesis is a highly coordinated and complex process that requires numerous assembly factors that ensure prompt and flawless maturation of ribosomal subunits. Despite the increasing amount of data collected, the exact role of most assembly factors and mechanistic details of their operation remain unclear, mainly due to the shortage of high-resolution structural information. Here, using cryo-electron microscopy, we characterized 30S ribosomal particles isolated from an Escherichia coli strain with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…2b and Supplementary Video 2 ), which is enabled by a pivot point between the KH-like domain and CTD. The conformational change appears to be a unique feature of RBFA, which was not reported for bacterial counterparts 10 , 25 . METTL15 would clash with RBFA-in from pre-SSU-2 (Extended Data Fig.…”
Section: Mainmentioning
confidence: 73%
“…2b and Supplementary Video 2 ), which is enabled by a pivot point between the KH-like domain and CTD. The conformational change appears to be a unique feature of RBFA, which was not reported for bacterial counterparts 10 , 25 . METTL15 would clash with RBFA-in from pre-SSU-2 (Extended Data Fig.…”
Section: Mainmentioning
confidence: 73%
“…RbfA is associated with 16S rRNA but not 70S ribosomes or polysomes, and is essential in late-30S ribosomal subunit maturation [ 27 ]. Recently, RbfA and RimM were found to be involved in two distinct 30S assembly stages consisting of the early development of the central pseudoknot with the folding of the head and further docking of helix 44 to form important inter-subunit bridges in the mature structure at a later stage [ 28 ]. A comprehensive review revealed that increased RbfA synthesis could moderately attenuate △ rimM mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Maksimova, Korepanov, Kravchenko, Baymukhametov, Myasnikov, Vassilenko, Afonina, and Stolboushkina classified the bacterial 30S ribosomal subunit according to structure in response to depleting the assembly factor RbfA. The results indicate that RpfA stabilizes the 30S pseudoknot (a universal feature of the small ribosomal subunit across the evolutionary spectrum) and assists the docking of 16S rRNA Helix 44 into the decoding center [ 21 ].…”
Section: The Volumementioning
confidence: 99%